Risk aversion in multilevel electricity market models with different congestion pricing regimes - Ambrosius, Mirjam; Egerer, Jonas; Grimm, Veronika; van der Weijde, Adriaan H. (Energy Economics, 2022)
Due to ongoing efforts for decarbonization, electricity markets worldwide are undergoing fundamental transitions, which result in increased uncertainty for all market participants. Against this background, we investigate the impact of risk aversion on investment and market operation in markets with different congestion pricing regimes and multi-level decision making. We develop a stochastic multi-level equilibrium model with risk-averse agents, which includes investment in transmission and generation capacity, market operation, and redispatch. The model can incorporate perfect, as well as imperfect locational price signals and different upper-level expectations about lower-level risk aversion. We apply our model to a stylized two-node example and compare the effects of risk aversion in a system with zonal and nodal pricing, respectively. Our results show that the effect of risk aversion is more pronounced in a market with nodal pricing, compared to a market with imperfect locational price signals. Furthermore, transmission planners that are ignorant about risk aversion of generation companies can induce substantial additional costs, especially in a nodal pricing marke
Keywords: OR in energy; risk-averse investment; stochastic programming; electricity market modeling; multilevel optimization